2021
DOI: 10.1177/1049732321993443
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators That Influence Providers’ Ability to Educate, Monitor, and Treat Substance Use in First-Episode Psychosis Programs Using the Theoretical Domains Framework

Abstract: In this qualitative study, we explore providers’ experiences with addressing substance use among individuals with first-episode psychosis (FEP) enrolled in coordinated specialty care (CSC) programs. Three focus groups were conducted with 24 providers from CSC programs for FEP in Washington. Questions were focused on barriers and facilitators to addressing substance use using the Theoretical Domains Framework (TDF) as a guide. Thematic analysis was used to code all transcripts. Identified TDF domains were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…At the provider-level, the challenges and need for training to address high rates of substance use among individuals with FEP was also a point of concern, which is consistent with prior research (Oluwoye & Fraser, 2021 ; Oluwoye et al, 2019 ). The CSC model used in the five programs that participated in the present study includes a substance use module focused on harm reduction in the individual therapy component of the program.…”
Section: Discussionsupporting
confidence: 79%
“…At the provider-level, the challenges and need for training to address high rates of substance use among individuals with FEP was also a point of concern, which is consistent with prior research (Oluwoye & Fraser, 2021 ; Oluwoye et al, 2019 ). The CSC model used in the five programs that participated in the present study includes a substance use module focused on harm reduction in the individual therapy component of the program.…”
Section: Discussionsupporting
confidence: 79%
“…Substance use has consistently been associated with disengagement from services (Kreyenbuhl et al, 2009; Mascayano et al, 2021). For instance, a recent quantitative study found that cannabis and alcohol use reduced the likelihood of graduating from CSC (Oluwoye & Fraser, 2021). The findings presented in the present study extend previous research by illustrating how substance use impacts engagement in individual psychotherapy by increasing symptoms and decreasing motivation to meaningfully engage in sessions.…”
Section: Discussionmentioning
confidence: 99%
“…All participants emphasized their desire to know more about SU and effective treatment approaches. One study suggested that professionals trained in SU treatment, for example, certified SU and addiction specialists, could be incorporated into CSC teams (Oluwoye & Fraser, 2021). To date, research of teams with a recovery/SU specialist role has not been published, although qualitative work reveals that providers feel this would be a useful additional role (Stokes et al, 2022), and CSC teams in several states have SU specialist roles (Bello & Dixon, 2022).…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%